Double Gold/Nitrogen Nanosecond-Laser-Doping of Gold-Coated Silicon Wafer Surfaces in Liquid Nitrogen - Sergey Kudryashov; Alena Nastulyavichus; Victoria Pryakhina; Evgenia Ulturgasheva; Michael Kovalev; Ivan Podlesnykh; Nikita Stsepuro; Vadim Shakhnov (Technologies)
A novel double-impurity doping process for silicon (Si) surfaces was developed, utilizing nanosecond-laser melting of an 11 nm thick gold (Au) top film and a Si wafer substrate in a laser plasma-activated liquid nitrogen (LN) environment. Scanning electron microscopy revealed a fluence- and exposure-independent surface micro-spike topography, while energy-dispersive X-ray spectroscopy identified minor Au (~0.05 at. %) and major N (~1–2 at. %) dopants localized within a 0.5 μm thick surface layer and the slight surface post-oxidation of the micro-relief (oxygen (O), ~1.5–2.5 at. %). X-ray photoelectron spectroscopy was used to identify the bound surface (SiNx) and bulk doping chemical states of the introduced nitrogen (~10 at. %) and the metallic (<0.01 at. %) and cluster (<0.1 at. %) forms of the gold dopant, and it was used to evaluate their depth distributions, which were strongly affected by the competition between gold dopants due to their marginal local concentrations and the other more abundant dopants (N, O). In this study, 532 nm Raman microspectroscopy indicated a slight reduction in the crystalline order revealed in the second-order Si phonon band; the tensile stresses or nanoscale dimensions of the resolidified Si nano-crystallites envisioned by the main Si optical–phonon peak; a negligible a-Si abundance; and a low-wavenumber peak of the Si3N4 structure. In contrast, Fourier transform infrared (FT-IR) reflectance and transmittance studies exhibited only broad structureless absorption bands in the range of 600–5500 cm−1 related to dopant absorption and light trapping in the surface micro-relief. The room-temperature electrical characteristics of the laser double-doped Si layer—a high carrier mobility of 1050 cm2/Vs and background carrier sheet concentration of ~2 × 1010 cm−2 (bulk concentration ~1014–1015 cm−3)—are superior to previously reported parameters of similar nitrogen-implanted/annealed Si samples. This novel facile double-element laser-doping procedure paves the way to local maskless on-demand introductions of multiple intra-gap intermediate donor and acceptor bands in Si, providing related multi-wavelength IR photoconductivity for optoelectronic applications.